2018
DOI: 10.5194/acp-18-7237-2018
|View full text |Cite
|
Sign up to set email alerts
|

Competition for water vapour results in suppression of ice formation in mixed-phase clouds

Abstract: Abstract. The formation of ice in clouds can initiate precipitation and influence a cloud's reflectivity and lifetime, affecting climate to a highly uncertain degree. Nucleation of ice at elevated temperatures requires an ice nucleating particle (INP), which results in so-called heterogeneous freezing. Previously reported measurements for the ability of a particle to nucleate ice have been made in the absence of other aerosol which will act as cloud condensation nuclei (CCN) and are ubiquitous in the atmospher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Biological particles, including bacteria, which are found in the atmosphere in various forms but at relatively low number concentrations (Despres et al, 2012), might play an important role globally as CCN or INPs (Morris et al, 2004;Möhler et al, 2007). While a large body of work on the ice nucleating (IN) activity of biological particles exists, the extent of their role in ice formation within modestly supercooled clouds remains poorly constrained (Murray et al, 2012;DeMott and Prenni, 2010;Möhler et al, 2007;Hoose et al, 2010;Spracklen and Heald, 2014;Phillips et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Biological particles, including bacteria, which are found in the atmosphere in various forms but at relatively low number concentrations (Despres et al, 2012), might play an important role globally as CCN or INPs (Morris et al, 2004;Möhler et al, 2007). While a large body of work on the ice nucleating (IN) activity of biological particles exists, the extent of their role in ice formation within modestly supercooled clouds remains poorly constrained (Murray et al, 2012;DeMott and Prenni, 2010;Möhler et al, 2007;Hoose et al, 2010;Spracklen and Heald, 2014;Phillips et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For a given temperature, observed MPR ice increases slightly with RH. Simpson et al () reported that CCN activation can outcompete INP for water vapor and result in the suppression of ice formation in mixed phase clouds. Therefore, low RH is often associated with weak updrafts or even downdrafts, which leads to the suppression of immersion freezing to form ice crystals and results in lower MPR ice .…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneous nucleation occurs at lower levels of supersaturation and higher temperatures than homogeneous nucleation [13,14]. Heterogeneous ice nucleation plays an important role in mixed-phase clouds since it affects the allocation of water between the ice and liquid phases [15,16]. Furthermore, it establishes the duration, radiative impact, and precipitation of clouds [17].…”
Section: Introductionmentioning
confidence: 99%